2019
DOI: 10.1002/ange.201900307
|View full text |Cite
|
Sign up to set email alerts
|

Platforms for Stable Carbon‐Centered Radicals

Abstract: Organic radicals can potentially play important roles in functional materials owing to an unpaired electron, but they are usually highly reactive and difficult to use. Therefore, stabilization of organic radicals is important. Among organic radicals, carbon‐centered radicals are promising because of their trivalent nature, which enables structural diversity and elaborate designs, but they are also less stable because of the reactivities towards carbon–carbon bond formation and atmospheric oxygen. Recently, sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 149 publications
0
8
0
Order By: Relevance
“…1,2,3 This class of compounds has also received increasing attention in materials science, because of the possibility to combine electron and spin conduction in molecular electronics such as organic light-emitting diodes (OLEDs), organic fieldeffect transistors (OFETs), and organic magnets. 4,5,6,7,8,9,10,11,12,13,14,15,16,17 In this context, organic diradicals are of particular interest since they can adopt two different spin states, namely singlet and triplet, related to the interaction between the unpaired electrons within the molecular backbone. 4,18 Organic conjugated radicals also allow to gain fundamental insights on the nature of chemical bonds and their delocalization, in addition to their other features such as narrow HOMO-LUMO energy gaps, low-lying doubly-excited states, and redox amphoterism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,3 This class of compounds has also received increasing attention in materials science, because of the possibility to combine electron and spin conduction in molecular electronics such as organic light-emitting diodes (OLEDs), organic fieldeffect transistors (OFETs), and organic magnets. 4,5,6,7,8,9,10,11,12,13,14,15,16,17 In this context, organic diradicals are of particular interest since they can adopt two different spin states, namely singlet and triplet, related to the interaction between the unpaired electrons within the molecular backbone. 4,18 Organic conjugated radicals also allow to gain fundamental insights on the nature of chemical bonds and their delocalization, in addition to their other features such as narrow HOMO-LUMO energy gaps, low-lying doubly-excited states, and redox amphoterism.…”
Section: Introductionmentioning
confidence: 99%
“…24,25,27,28 So far, the chemical and configurational stabilities issues have been overcome using mainly two strategies: Shielding the unpaired electrons with bulky substituents, or enhancing their delocalization over the molecular backbone. 8,9,27,35,36,37,38 While such approaches can be efficient, they often require additional synthetic steps and may preclude significant intermolecular interactions for charge and spin transport applications. 17 Recently, theoretical and experimental studies have reported that the stability of radicals can be considerably enhanced if they are in an uncommon electronic configuration, such that the energy of the singly occupied molecular orbital (SOMO) is below the highest doubly occupied molecular orbital (HOMO) level (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of bulky substituents such as trioxotriangulene, cyclopentadienyls, and triphenylmethyl around the radicals is an effective strategy to improve the stability, which provides steric hindrance effect and electron resonance effect to efficiently suppress the side reaction of the unpaired electrons . Appropriate incorporation of electron-donating and electron-withdrawing groups (like porphyrins, dicyanomethyls, and alkyl-amino-carbenes) provided the radicals with improved stability by inductive and conjugative effects . By combining the above merits of those substituents groups, the precisely designed organic structure can inhibit the of unpaired electrons because of the formation of chemical bonds .…”
Section: Introductionmentioning
confidence: 99%
“…28 Appropriate incorporation of electron-donating and electronwithdrawing groups (like porphyrins, 29 dicyanomethyls, 30 and alkyl-amino-carbenes 31 ) provided the radicals with improved stability by inductive and conjugative effects. 32 By combining the above merits of those substituents groups, 33 the precisely designed organic structure can inhibit the of unpaired electrons because of the formation of chemical bonds. 34 Among various organic materials, 35 covalent triazine frameworks (CTFs) possess bulky protecting groups and conjugated frameworks, which are expected to extremely stabilize the radicals during the redox processes and enhance electrochemical performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[4] Studies on dicyanomethyl radicals have gained increasing attention owing to their dynamic covalent behaviors to exist as a stable radical or form molecular self-assemblies through a clean radical-radical coupling process. [5][6][7][8] It has been shown that dicyanomethyl radicals show their reactivities depending upon their stabilities. We reported that meso-subporphyrinylsubstituted dicyanomethyl radical 1 [8a] and meso-porphyrinylsubstituted dicyanomethyl radical 2 [8b] are both stable and do not undergo any dimerization reaction but b-porphyrinylsubstituted dicyanomethyl radicals 3 [8b] can be isolated as stable s-dimers (3) 2 .…”
mentioning
confidence: 99%